1968
DOI: 10.2135/cropsci1968.0011183x000800030013x
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Architecture at Various Population Densities and the Growth and Grain Yield of Corn1

Abstract: Parameters of canopy architecture were related to light interception and productivity using data from a field experiment with corn grown at population densities from 17,500 to 125,000 plants per hectare. With nutrients and soil moisture nonlimiting, the amount of solar radiation intercepted by the foliage canopy was a major determinant of crop growth during the vegetative stage. Leaf arrangements with a preponderance of erect leaves, occurring just before the tassels emerged, allowed the deepest penetration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
1

Year Published

1971
1971
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 0 publications
5
55
0
1
Order By: Relevance
“…Maximum amounts of soluble solids usually have accumulated 3-4 weeks after anthesis (Welton et al 1930; Van Reen and Singleton 1952;Campbell 1964; Williams et al 1968; and Campbell and Hume 1970) and rapid declines in stalk soluble solids often occurred during the grain-filling period (Da;inard et al 1969 Similar results were obtained in this study.…”
Section: Introductionsupporting
confidence: 82%
“…Maximum amounts of soluble solids usually have accumulated 3-4 weeks after anthesis (Welton et al 1930; Van Reen and Singleton 1952;Campbell 1964; Williams et al 1968; and Campbell and Hume 1970) and rapid declines in stalk soluble solids often occurred during the grain-filling period (Da;inard et al 1969 Similar results were obtained in this study.…”
Section: Introductionsupporting
confidence: 82%
“…The smaller value is similar to our highest field observations ( Table 1) and corres ponds to an efficiency in energy conversion of 3% of the total irradiance. The simulations matched seasonal growth curves (75,144,256). The theoret- • After Cooper's review (48).…”
Section: Productivity Ratesmentioning
confidence: 79%
“…Alvino et al [196] reported that the fraction of light absorbed by leaves, which controls crop growth rate, plant development, crop biomass accumulation, is directly related to the interception of solar radiation, up to the critical LAI [197]. The light distribution within the canopy affects, inter alia, the photosynthetic efficiency.…”
Section: Sunlit and Shade Leavesmentioning
confidence: 99%